Firm History and Managerial Entrenchment: Empirical Evidence for Vietnam Listed Firms - Pham, Lan Le-Phuong; Vo, Duc Hong; Nguyen, Thang Cong; McAleer, Michael (Journal of Reviews on Global Economics, 2019)
Managerial entrenchment occurs when managers are able to manipulate financing decisions to support their own interests rather than those of shareholders. Such possible actions can involve deception and fraud. Furthermore, the market timing activity is explained by managers' financing decisions through which companies choose to raise debt or equity to finance their investment opportunities. Nevertheless, the relationship between managerial entrenchment and leverage ratio, together with the link between market timing and leverage ratio, have not been considered carefully and investigated in the Vietnamese context. The paper provides empirical evidence of the effect of managerial entrenchment and market timing through firms' histories on leverage ratio in Vietnam using a sample of 289 non-financial firms listed on the Ho Chi Minh Stock Exchange (HOSE) during the period 2006-2017. OLS, GMM and the endogenous switching methods are used for estimating the models. Findings from the paper indicate that there is a negative relationship between managerial entrenchment and leverage ratio, and that there is a negative effect of firm history, including financial deficit, various timing measures, and stock price history on the leverage ratios of Vietnam's listed firms.